2005
DOI: 10.2203/dose-response.003.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of Persistent Organic Pollutants: Possible Mode(S) of Action and Further Considerations

Abstract: Persistent organic pollutants (POPs) are long-lived toxic organic compounds and are of major concern for human and ecosystem health. Although the use of most POPs is banned in most countries, some organochlorine pesticides are still being used in several parts of the world. Although environmental levels of some POPs such as polychlorinated biphenyls (PCBs) have declined, newly emerging POPs such as polybrominated diphenyl ethers (PBDEs) have been increasing considerably. Exposure to POPs has been associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 154 publications
2
101
0
2
Order By: Relevance
“…And PCB 11 was reported as a dominant component in some places (King et al, 2002;Rodenburg et al, 2010;Baek et al, 2013;Grossman, 2013), even made the total PCBs concentration exceed the local standard in the Delaware River (Rodenburg et al, 2010). Some studies suggested that PCB 11 had some potentially toxic activities like calcium, dopamine, and thyroid hormone interference (Shain et al, 1991;Kodavanti, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…And PCB 11 was reported as a dominant component in some places (King et al, 2002;Rodenburg et al, 2010;Baek et al, 2013;Grossman, 2013), even made the total PCBs concentration exceed the local standard in the Delaware River (Rodenburg et al, 2010). Some studies suggested that PCB 11 had some potentially toxic activities like calcium, dopamine, and thyroid hormone interference (Shain et al, 1991;Kodavanti, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since NO participates in synaptic plasticity, neurite outgrowth and extension, synaptogenesis, neuronal proliferation and maturation (Holscher, 1997;Sanchez-Islas and Leon-Olea, 2004;Wu et al, 1994), the early PCB-induced changes in NOS activity may be associated with altered nervous system development and function (Kodavanti, 2005). Others have suggested that PCB-induced disruption of thyroid hormone signaling in PCB-exposed animals may explain the long-term effects of developmental PCB exposure on nervous system structure and function (Yang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Polychlorinated biphenyls (PCBs) are persistent organohalogen compounds of which chronic exposure can lead to endocrine disruption and neurotoxicity (Kodavanti, 2005;Kodavanti and Curras-Collazo, 2010). Although the manufacture of PCBs (including the high production industrial mixture, Aroclor 1254), was discontinued in 1977, PCBs are still found in significant quantities in the environment and human tissues including human breast milk (Lang, 1992;She et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…ПХБ -эндокринные дизрапторы. Они нару-шают функциональную деятельность щитовидной железы, снижая продукцию тиреоидных гормонов, печени и про-цессы обмена веществ, наиболее выраженные в прена-тальном периоде развития особи с последующим разви-тием детского ожирения и риском возникновения сахарного диабета [31,32]. Воздействие ПХБ в пренатальном периоде развития организма приводит к нарушениям половой диф-ференцировки гипоталамуса [33].…”
Section: биологическое действие эндокринных дизрапторов на живые оргаunclassified